Comparison of enteral prucalopride versus intravenous metoclopramide for feeding intolerance in patients with critical illness: a randomized double-blinded study - Elmokadem, Eman Mohamed; Abou El Fadl, Dina Khaled; Eissa, Nermin; Alnassar, Najla Abdulaziz; Bassiouny, Ahmed M.; Hanna Samy, Amir Eskander; El Said, Nouran Omar (Frontiers in Pharmacology, 2024)
Background: Feeding intolerance is commonly experienced during enteral feeding, necessitating cessation. Metoclopramide may be given to assist gastric emptying, but patients experience adverse effects and gradual loss of efficacy. Prucalopride, a safer prokinetic, may play a role in gastric emptying. Therefore, the current study aimed to assess its effectiveness and safety in feeding intolerance developed in critically ill patients.In this prospective randomized double-blinded study, patients with feeding intolerance were randomized to receive 2 mg prucalopride enterally once daily or 10 mg metoclopramide intravenously every 6-8 hours for seven days. Patients were monitored for treatment failure, successful feeding, gastric residual volume (GRV), and the development of medication-related adverse effects.Results: A total of 70 patients (35 in the metoclopramide group and 35 in the prucalopride group) completed the study. The average daily GRV in the prucalopride group was significantly lower compared to the metoclopramide group (p=<0.001) on day 7. Additionally, the percentage change in GRV from day 1 to day 7 showed a greater significant change in the prucalopride arm versus the metoclopramide arm (p=<0.001). The treatment groups were comparable in terms of ICU length of stay (p=0.094). Moreover, there was a significantly higher successful caloric intake in the prucalopride group compared to the metoclopramide group on day 7(p=0.039).Prucalopride administration in enterally fed patients with feeding intolerance may reduce GRV and improve feeding success rates compared to metoclopramide treatment. The use of prucalopride was found to be tolerable and safe in critically ill patients.ClinicalTrials.gov Identifier: NCT05496179